Social ties and open innovation: impacts on innovation capability - Nadia Carvalho; Hélio Zanquetto-Filho; Valmir Emil Hoffmann; Adonai José Lacruz (Innovation & Management Review, 2025)
This article investigates the impact of relational social capital (RSC) and relational risk perception (RRP) on innovation openness (IO) and examines whether innovation openness serves as a precursor to organizations' innovation capability (IC).The authors conducted a survey with 189 Brazilian companies operating within technology parks. Covariance-based structural equation modeling (CB-SEM) was employed to test the proposed conceptual framework.The results reveal that RSC positively influences IO, while RRP tends to reduce openness. The analysis of relational aspects demonstrates that open innovation significantly contributes to the development of innovation capabilities. Furthermore, the presence of relational intensity enhances the effectiveness of RSC on IO and fosters the development of innovative skills.This study broadens the discussion on the dynamics of interorganizational relationships by exploring the interplay between relational aspects and open innovation in the development of capabilities. Additionally, it provides managers with a framework to assess their organization's innovation processes through relational perspectives, enabling them to maximize innovation capabilities.This research addresses the conditions under which relationships are influenced by relational aspects, introducing relational intensity as a moderator in the proposed model between RSC-IO and IO-IC. It also explores the interconnections among RSC, RRP, IO, and IC, offering a comprehensive analysis of their combined impact.
Keywords: 650; Open innovation; Innovation capability; Relational social capital; Relational risk; Relational intensity